PARIWISATA CAGAR BUDAYA BENTENG PENDEM NGAWI - karyoto karyoto (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
This research was conducted on the basis of existing facts, in the area of ​​the Regional Government of Ngawi Regency, East Java Province, there is one plot of land covering an area of: 158,798 M2 on which there is a building that was a legacy of the Dutch Knil Army, when the Dutch colonized Indonesia, namely Fort Pendem Ngawi.Pendem Ngawi Fortress by the Dutch, used as the headquarters of the Dutch Knil Army, to maintain colonial power in Indonesia, the location of the fort is located in Pelem Village, Ngawi District, Ngawi Regency, East Java Province, Indonesia.At the time of this research, the location of the land and buildings of the Pendem Ngawi Fortress, since Indonesian Independence on August 17, 1945, changed the ownership status from the Dutch Colonial to become the State assets / State Property of the Republic of Indonesia, in the past it was used for the Armed Para Ngawi Battalion, now it is Tourism locations for the public.Building Pandem Ngawi Fortress, in 1950 the Ministry of Defense of the Republic of Indonesia carried out mapping and drawing of land plans and buildings together with the Office of the National Land Agency (BPN) of Ngawi Regency, formerly known as the Head of the Land Registration Office (KKP) - Ngawi Agrarian Office.The ownership of the Pendem Ngawi Fort building becomes the State asset / wealth of the Republic of Indonesia, based on the Perpu No. 23 of 1959 concerning the Repeal of Law No. 74 year 1957 and set the State of Danger.The problems that will be studied are: Pendem Ngawi Fort becomes a public tourism and cultural heritage place.